Investment Choices in the Young Generation: A Behavioral Economics Approach Using Prospect Theory - Andi Naila Quin Azisah Alisyahbana; Maria Reski; Andi Amrullah (Global Research Collaboration, 2024)
This study aims to explore the psychological and behavioral factors that influence investment decisions among students of the Faculty of Economics and Business at UNM using the Prospect Theory approach. This research is descriptive and utilizes a quantitative methodology, with the population consisting of students from the Faculty of Economics and Business at UNM. Data were collected using a questionnaire designed based on the principles of Prospect Theory in behavioral economics. The data analysis was conducted using statistical techniques, including descriptive statistical tests, to identify the factors influencing students' investment decisions. The findings reveal that students' financial decision-making behavior is significantly influenced by various psychological factors. The research indicates that students tend to be consistent in their financial decision-making processes, demonstrating a notable influence of behavioral biases. Additionally, the study highlights that common behavioral biases, such as risk aversion and loss aversion, are prevalent among students when making investment decisions. These results emphasize the importance of understanding the psychological aspects of investment choices, suggesting that educational initiatives should focus on improving students' awareness of these biases to foster more informed and rational investment behavior.